2020
DOI: 10.3390/f11050573
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Salicylate and Sesquiterpene Emissions Are Indicative for Aphid Infestation on Scots Pine

Abstract: Biotic stresses on forest trees are caused by various pest insects and plant pathogens. Attack by these parasites is known to induce the emissions of various biogenic volatile organic compounds (BVOCs), and the profile of these emissions often differs between infested and healthy plants. This difference in emission profile can be used for the non-destructive early-stage diagnosis of the stressor organism. We studied how phloem feeding by a large pine aphid (Cinara pinea Mordvilko) on the branch bark of Scots p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…As olfactory cues, we used two HIPVs, methyl salicylate (MeSA) and methyl jasmonate (MeJA). These are well-known substances produced by a wide range of plant species in response to herbivory or other stressors; MeJA is linked to damage by chewing herbivores like caterpillars and MeSA to sap-sucking herbivores like aphids (Thaler, 1999;Moreira et al, 2018;Kivimäenpää et al, 2020). They are known to attract predatory insects (e.g., James and Price, 2004;Simpson et al, 2011), and appear also to be detectable by insectivorous birds in the field (Mrazova and Sam, 2017;Hiltpold and Shriver, 2018;Rubene et al, 2019).…”
Section: Visual and Olfactory Cuesmentioning
confidence: 99%
“…As olfactory cues, we used two HIPVs, methyl salicylate (MeSA) and methyl jasmonate (MeJA). These are well-known substances produced by a wide range of plant species in response to herbivory or other stressors; MeJA is linked to damage by chewing herbivores like caterpillars and MeSA to sap-sucking herbivores like aphids (Thaler, 1999;Moreira et al, 2018;Kivimäenpää et al, 2020). They are known to attract predatory insects (e.g., James and Price, 2004;Simpson et al, 2011), and appear also to be detectable by insectivorous birds in the field (Mrazova and Sam, 2017;Hiltpold and Shriver, 2018;Rubene et al, 2019).…”
Section: Visual and Olfactory Cuesmentioning
confidence: 99%
“…Although there have been numerous studies on plants in general [ 114 ], very few studies have explicitly investigated the effects of piercing–sucking herbivores on BVOC emissions of boreal trees. Kivimäenpää et al [ 106 ] showed that P. sylvestris infested by the aphid Cinara pinea Mordvilko, had significantly increased emissions of methyl salicylate (MeSA) and SQTs, but MT emissions were not affected. In a study of B. pendula and A. glutinosa by Blande et al [ 107 ], some induced terpene emissions were recorded, but the most notable aphid-induced emission was MeSA.…”
Section: Herbivore Feeding and Oviposition Effects On Bvoc Emissionsmentioning
confidence: 99%
“…In a study of B. pendula and A. glutinosa by Blande et al [ 107 ], some induced terpene emissions were recorded, but the most notable aphid-induced emission was MeSA. These two studies indicate that aphid-feeding characteristically induces emissions of MeSA which appear to be dependent on aphid density [ 106 ] and duration of infestation [ 107 ].…”
Section: Herbivore Feeding and Oviposition Effects On Bvoc Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, trees and shrubs emitted (E)-2-hexenal upon wounding and in response to bacterial pathogenesis [6]. Emissions of Pinus sylvestris saplings infected with large pine aphid (Cinara pinea Mordviko) contained methyl salicylate and (Z)-3-hexenyl acetate [75]. Plants infected with pathogens probably emit methyl salicylate to activate disease resistance in neighboring plants and healthy tissues of the emitting plant [7].…”
Section: Sources Of Glv 21 Reasons or Causes Of Emissionmentioning
confidence: 99%